Plastics Housewares Made of Styron: Color Cues for Smart Kitchens! - Dow Chemical Company (1950)
Color print advertisement for Styron, the trade name for Styrenic plastics historically manufactured and sold by the Dow Chemical Company for a variety of consumer applications, including packaging and food service, appliances, and other plastic wares. The advertisement features a woman in a kitchen framed by assorted brightly-colored housewares made of Styron. This advertisement appeared in a 1950 edition of Ladies' Home Journal.
Keywords: Dow Chemical Company; Advertising; Corporations; Chemical industry; Plastics; Plastics industry and trade; Housewives; Housewives as consumers; Women in advertising; Advertising, Industrial; Consumer goods